2019
DOI: 10.1021/acsnano.8b09198
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale and Low-Cost Fabrication of Silicon Mie Resonators

Abstract: High index dielectric nanoparticles have been proposed for many different applications. However, widespread utilization in practice also requires large-scale production methods for crystalline silicon nanoparticles, with engineered optical properties in a low-cost manner.Here, we demonstrate a facile, low-cost, and large-scale fabrication method of crystalline silicon colloidal Mie resonators in water, using a blender. The obtained nanoparticles are polydisperse with an almost spherical shape and the diameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 52 publications
2
48
0
Order By: Relevance
“…In this study, the synthesized AgNPs have been confirmed with some functional groups stabilized on the surface, which provides extra shells to the AgNPs, leading to a larger d H through DLS method than the d S through TEM [58], as shown in electronic supplementary material, figure S2, and similar results have been reported in the previous studies [34,59,60].…”
Section: Characterization Of Silver Nanoparticlessupporting
confidence: 85%
“…In this study, the synthesized AgNPs have been confirmed with some functional groups stabilized on the surface, which provides extra shells to the AgNPs, leading to a larger d H through DLS method than the d S through TEM [58], as shown in electronic supplementary material, figure S2, and similar results have been reported in the previous studies [34,59,60].…”
Section: Characterization Of Silver Nanoparticlessupporting
confidence: 85%
“…c–e) Reproduced with permission. [ 39 ] Copyright 2019, American Chemical Society. f–h) Reproduced with permission.…”
Section: Fabrications Of Colloidal Mie Resonatorsmentioning
confidence: 99%
“…Chaâbani et al demonstrated that crystalline Si nanoparticles 100–200 nm in diameters can be produced by crashing Si lumps in water using a kitchen blender (Figure 3c), followed by size separation by centrifugation. [ 39 ] This method provides a facile, low‐cost, and large‐scale fabrication of crystalline Si Mie resonators. However, the size and shape distributions are inevitably large and the circularity of the particles is 81% (Figure 3d,e), which is smaller than those of typical colloidal metal nanoparticles (≈90%).…”
Section: Fabrications Of Colloidal Mie Resonatorsmentioning
confidence: 99%
“…We used an averaged refractive index approach in order to perform side illumination in simulations to avoid the possible numerical artifacts in FDTD caused by the injection of the light simultaneously in different media (glass-air). The effective refractive index was taken to be 1.25 [44]. By illumination from the side we can excite the quadrupolar mode by creating a phase variation along the base of the nanocylinder [33,45].…”
Section: Resultsmentioning
confidence: 99%